The kinks in charge radii across N = 82 and 126 revisited. (20th May 2021) - Bhuyan, M; Maheshwari, B; Kassim, H A; Yusof, N; Patra, S K; Carlson, B V; Stevenson, P D
Abstract: We revisit the studies of the isotopic shift in the charge radii of even–even isotopes of Sn and Pb nuclei at N = 82, and 126, respectively, within the relativistic mean-field (RMF) and relativistic-Hartree–Bogoliubov (RHB) approach. The shell model is also used to estimate isotopic shift in these nuclei, for the first time, to the best of our knowledge. The ground state single-particle energies (SPEs) are calculated for non-linear NL3 and NL3* and density-dependent DD-ME2 parameter sets compared with the experimental data, wherever available. We establish a correlation between the filling of single-particle levels and the isotopic shift in occupation probabilities. The obtained SPE from the RMF and RHB approaches are in line with those used in the shell model and experimental data for both the Sn and Pb isotopic chains. The shell model calculated isotopic shift agrees with RMF and RHB approaches that explain the experimental data quite well in case the of Pb nuclei beyond N =126.